The whole machinery : the rural modern in cultures of the U.S. South, 1890-1946 - Child, Ben (Athens [Georgia] : The University of Georgia Press, 2019)
A familiar story holds that modernization radiates out from metropolitan origins. The whole machinery explores representations of people and places, objects and occasions, that reverse that trajectory, demonstrating how modernizing agents move in a contrary direction as well--from the country to city. In a crucial reversal, these figures aren't pulled by or into urban modernity so much as they bring alternate--and transformative--iterations of the modern to the urban world. This book upends the U.S. South's reputation as retrograde and unresponsive to modernity by showing how the effects of national and transnational exchange (particularly via the cotton trade), emergent technologies, and industrialization animate environments and bodies associated with, or performing, versions of the rural. To this end, it also searches out the shadow side of the cosmopolitan modern by investigating the rural sources--the laboring bodies and raw materials--that made such urban spaces possible. The whole machinery explores a range of canonical and noncanonical figures: Paul Laurence Dunbar, Frances E.W. Harper, W.E.B. Du Bois, Allen Tate, Don West, the authors of the Southern Tenant Farmers' Union pamphlet The Disinherited Speak, Charlie Poole, and Zora Neale Hurston among them. It uncovers signs of the rural modern in a variety of texts and media, including narrative fiction and poetry, as well as photographs, sound recordings, radio broadcasts, letters, newspaper reports, and magazine profiles. These readings convey diverse and individuated desires for escape or entrenchment, often in the same conflicted voice, ultimately creating multivalent expressions and experiences of rurality that are, in their way, as thoroughly modern as those of more widely canonized urban figures.
Introduction. Limning the land -- Cultures of black agriculture -- "The true reconstruction of the country" in Iola Leroy and the plantation -- Poems of Paul Laurence Dunbar -- "Strange vicissitudes": dirt, progress, and the modern -- Other agrarian -- Making it old in the New South; or, The leisure agrarians cultivate the folk -- Disinherited speech acts: the body as archive in labor agrarianism -- Migratory modernism -- Station to station: New York City and the returns of the rural -- Coda. Uneven ground.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on November 20, 2019).
eBooks on EBSCOhost
Keywords: American literature -- Southern States -- History and criticism; Rural conditions in literature; Civilization, Modern, in literature; Conditions rurales dans la littérature.; LITERARY CRITICISM -- American -- General; American literature; Civilization, Modern, in literature; Rural conditions in literature; Southern States; Electronic books; Criticism, interpretation, etc